How Xylella fastidiosa subsp. pauca influences endophytic communities and plant physiology in resistant and susceptible olive tree cultivars - Marzia Vergine; Federico Vita; Mariarosaria De Pascali; Giambattista Carluccio; Erika Sabella; Alessandro Passera; Paola Casati; Luigi De Bellis; Andrea Luvisi (Plant Stress)
This study explores the interaction between endophytic communities and olive trees (Olea europaea L.) infected by Xylella fastidiosa subsp. pauca (Xfp), the causal agent of Olive Quick Decline Syndrome (OQDS). A multidisciplinary approach was used to assess physiological markers (malondialdehyde, proline, total phenolics and flavonoids), pigment contents (Chl a, Chl b, carotenoids), relative water content (RWC), enzymatic activities (APX, CAT, T-SOD) as well as the diversity and composition of endophytes, in resistant (Leccino) and susceptible (Cellina di Nardò) olive cultivars at varying levels of Xfp infection. Trees were sampled in naturally infected orchards in Apulia (Southern Italy) and grouped by Xfp titer: control (≤10² cfu/mL), low (10³–10⁵), and high (≥10⁶).The results show consistent titer-dependent changes: pigment content and RWC decreased with increasing infection, while stress markers and carotenoids increased. High-throughput sequencing of 16S rRNA and ITS regions revealed significant differences in microbial communities.The Cellina microbiome appeared highly variable and sensitive to infection levels, whereas Leccino exhibited a higher abundance and diversity of beneficial endophytes, including those known to produce antimicrobial compounds and promote plant health. Malondialdehyde data suggest lower oxidative damage in Leccino, reflecting enhanced stress tolerance. In contrast, the compromised endophytic structure in Cellina may exacerbate its vulnerability to Xfp. These findings suggest that Xfp modulates plant metabolism and, in turn, the endophytic community composition by inducing physiological changes in the host plant to counteract pathogen activity. These alterations may affect natural defence mechanisms, including the potential role of specific endophytes in enhancing resistance to Xfp.